Strengthening global midwifery education to improve quality maternity care: Co-designing the World Health Organization Midwifery Assessment Tool for Education (MATE) - Hunter, Billie; Thomas, Grace; Wilhelmová, Radka; Trendafilova, Petya; Blaževičienė, Aurelija; Lynch, Lynn; Jokinen, Mervi (Nurse education in practice, 2022)
AIMS: To describe a three-phase co-designed project to develop a culturally appropriate and relevant education assessment tool, and report on pilot and field-testing phases. BACKGROUND: High-quality midwifery education is essential for high-quality maternity care (WHO 2019); however midwifery education and maternity care vary in quality throughout Europe. To support countries in strengthening their midwifery education, World Health Organization (WHO) European Region commissioned development of the Midwifery Assessment Tool for Education (MATE). The tool was developed over three years, using an iterative, collaborative process with regional experts. Published by WHO in May 2020, MATE provides focused questions and evidence-informed resources to stimulate and inform discussions within country. DESIGN: Three-phase co-design approach to develop, pilot and field-test an education assessment tool. METHODS: Phase 1: initial development of MATE with expert midwifery support; Phase 2: MATE piloting workshops in Czech Republic and Lithuania focusing on clarity, usability and relevance; Phase 3: MATE field-testing workshop in Bulgaria exploring the process of using MATE and its effectiveness for generating discussion. Purposive selection of workshop participants ensured a broad range of perspectives: clinicians, educators, students, policy makers and service users. All participants were invited to give narrative feedback during workshops and via completion of a post-workshop online survey. The XX University Research Ethics Committee advised that formal ethical review was unnecessary. RESULTS: Feedback from collaborators in all phases indicated that engaging with MATE co-design and testing was a positive experience. A 'bottoms up' approach ensured that MATE content was relevant to regional needs, culturally acceptable and appropriate. Seventy-nine individuals participated in Phases 2 and 3 and all were sent a post-workshop online survey, with 31 responses (39 %). Qualitative and quantitative data indicated that the aim of MATE was well understood, and its usability and relevance were evaluated positively. In Phase 2, improvements to wording and format were suggested. MATE was subsequently amended prior to field testing. Phase 3 feedback indicated that MATE was highly effective for generating in-country dialogue and frank discussions about the future of midwifery education and practice. CONCLUSIONS: Using a co-design approach has ensured that MATE is culturally relevant, accessible and appropriate. This initial evaluation indicates that MATE can facilitate in-country dialogue and support the strengthening of midwifery education in accordance with WHO aims. Next steps are a fully evaluated trial of MATE in a selected partner country, where we will continue to work collaboratively to optimise engagement and ensure cultural appropriateness.
Keywords: Quality of Health Care; služby zdravotní péče o matku; Světová zdravotnická organizace; Midwifery; lidé; Female; Europe; babictví; Evropa; Pregnancy; těhotenství; Maternal Health Services; World Health Organization; kvalita zdravotní péče; ženské pohlaví; Humans